Pelaksanaan Distribusi Zakat Fitrah Perspektif Keadilan Distributif Yusuf Al-Qardhawi - Retno Novita Diningrum; Fuady Abdullah; Lilis Rohmawati; Rista Sasputri (Fakultas Syariah Institut Agama Islam Negeri Ponorogo, 2022)
Distribution of zakat fitrah at the Al-Muhajirin mosque, Mojorejo Village, Kebonsari District, Madiun Regency, evenly distributed to each group of zakat recipients. The committee distributed four mustahik groups: the needy, poor, amil, and fi sabilillah. In distributing zakat fitrah, the committee distributes it evenly with the same amount for each group. The distribution model at the Al-Muhajirin mosque is still equalized for each group, the distribution for the needy, the poor may be exaggerated because it is seen from the daily perspective of the recipient of zakat. There is no set rule, but it will be different for each person according to their circumstances. Based on research that has been carried out at the Al-Muhajirin Mosque, Mojorejo Village, Kebonsari District, Madiun Regency, it can be concluded: the practice of distributing zakat fitrah at the Al-Muhajirin Mosque is only distributed evenly with the same amount for each group. The distribution of zakat fitrah at the Al-Muhajirin mosque is not by Yusuf Al-Qardhawi's theory of distribution because the distribution is still equalized with the same amount, and does not see the needs of each recipient of zakat, ideally, the distribution is in the al-Muhajirin mosque committee determines the four groups who are entitled to receive zakat, in its distribution the committee prioritizes the poor group which is prioritized. We look at the size of the distribution of zakat to these groups in terms of inability from an economic standpoint because each individual has a minimal income, so it is very lacking to meet their daily needs. Pendistribusian zakat fitrah di masjid Al-Muhajirin Desa Mojorejo Kecamatan Kebonsari Kabupaten Madiun mendistribusikan secara merta setiap golongan penerima zakat. Panitia mendistribusikan empat golongan mustahik yaitu golongan fakir, miskin, amil dan fi sabilillah. Dalam pendistribusian zakat fitrah panitia mendistribusikan secara merata dengan jumlah yang sama setiap golongannya. Model pendistribusian di masjid Al-Muhajirin dalam pembagiannya masih di samaratakan setiap golongan individunya, pendistribusian bagi fakir,miskin boleh dilebihkan karena melihat dari segi kesehariannya si penerima zakat. Tidak ada suatu ketentuan yang dipastikan, tapi akan berbeda-beda untuk tiap orang sesuai dengan keadaan mereka. Berdasarkan penelitian yang sudah di lakukan di Masjid Al-Muhajirin Desa Mojorejo Kecamatan Kebonsari Kabupaten Madiun dapat di simpulkan: praktik pendistribusian zakat fitrah di Masjid Al-Muhajirin hanya di distribusikan secara merata dengan jumlah yang sama setiap golongannya. Pendistribusian zakat fitrah di masjid Al-Muhajirin belum sesuai dengan teori distribusi Yusuf Al-Qardhawi, karena dalam pendistribusiannya masih disama ratakan dengan jumlah yang sama, dan tidak melihat kebutuhan dari masing-masing penerima zakat, idealnya pendistribusian yang ada di masjid al-muhajirin panita menetukan empat golongan yang berhak menerima zakat, dalam pendistribusiannya panitia lebih mengutamakan golongan fakir miskin yang di prioritaskan. Ukuran pembagian zakat kepada golongan tersebut kita pandang segi ketidakmampuan dari sisi ekonomi, karena setiap individu memiliki penghasilan yang minim sehingga untuk memenuhi kebutuhan kesehariannya sangat kurang.